Molecular systematic analysis demonstrates that the threatened southern bell frog, Litoria raniformis (Anura: Pelodryadidae) of eastern Australia, comprises two sub-species - Vörös, Judit; Wassens, Skye; Price, Luke; Hunter, David; Myers, Steven; Armstrong, Kyle; Mahony, Michael J.; Donnellan, Stephen (Zootaxa, 2023)
In south-eastern Australia, the pelodryadid Litoria aurea Group (sensu Tyler & Davies 1978) comprises three species: Litoria aurea (Lesson, 1829), Litoria raniformis (Keferstein, 1867), and Litoria castanea (Steindachner, 1867). All three species have been subject to declines over recent decades and taxonomic uncertainty persists among populations on the tablelands in New South Wales. We address the systematics of the Group by analysing mitochondrial and nuclear DNA sequences to assess divergence in the Litoria raniformis from across its current range in New South Wales (NSW), Victoria, South Australia (SA) and Tasmania. We also included samples of Litoria castanea from a recently rediscovered population in the southern tablelands of NSW. Our phylogenetic and population genetic analyses show that Litoria raniformis comprises northern and southern lineages, showing deep mitochondrial DNA sequence divergence (7% net average sequence divergence) and can be diagnosed by fixed allelic differences at more than 4,000 SNP loci. Samples of the northern lineage were collected from the Murray-Darling Basin while those of the southern lineage were collected from south-eastern South Australia, southern and south-eastern Victoria and Tasmania. Analysis of the morphology and bioacoustics did not unequivocally delineate the two lineages. The presence of a hybrid backcross individual in western Victoria at the northern margin of the southern lineage, leads us to assign sub-species status to the two lineages, L. r. raniformis for the northern lineage and L. r. major for the southern lineage. Our data do not unequivocally resolve the taxonomic status of L. castanea which will require molecular genetic analyses of museum vouchers from those parts of the range where L. castanea and L. raniformis are no longer extant. Our data also suggest that human mediated movement of frogs may have occurred over the past 50 years. Our genotyping of vouchers collected in the 1970s from the Mount Lofty Ranges in South Australia detected mitochondrial haplotypes of both sub-species and SNP analysis showed that a single Tasmanian specimen was a backcross with L. r. raniformis ancestry. Movement of L. r. raniformis into Tasmania and both sub-species into the Mount Lofty Ranges are not likely due to passive movements of animals through agricultural commerce, but due to the attractiveness of the species as pets and subsequent escapes or releases, potentially of the larval life stage.